2019
DOI: 10.3389/fmicb.2019.01789
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Importance of Yeasts in Indigenous Fermented Food and Beverages Produced in Sub-Saharan Africa

Abstract: Indigenous fermented food and beverages represent a valuable cultural heritage in sub-Saharan Africa, having one of the richest selections of fermented food products in the world. In many of these indigenous spontaneously fermented food and beverages, yeasts are of significant importance. Several factors including raw materials, processing methods, hygienic conditions as well as the interactions between yeasts and other commensal microorganisms have been shown to influence yeast species diversity and successio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 134 publications
4
47
0
Order By: Relevance
“…The occurrence of diverse groups of yeasts in the products could, therefore, be associated with the breaking down of starch to increase the nutritional value of fermented and nonfermented cassava. The high prevalence of Candida and Saccharomyces in the products is consistent with studies elsewhere that reported them as the most dominant yeasts in many foods in sub-Saharan Africa [ 25 , 26 ]. Reports have shown that S. cerevisiae is the dominant yeast in the fermentation of most indigenous food products in sub-Saharan Africa [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The occurrence of diverse groups of yeasts in the products could, therefore, be associated with the breaking down of starch to increase the nutritional value of fermented and nonfermented cassava. The high prevalence of Candida and Saccharomyces in the products is consistent with studies elsewhere that reported them as the most dominant yeasts in many foods in sub-Saharan Africa [ 25 , 26 ]. Reports have shown that S. cerevisiae is the dominant yeast in the fermentation of most indigenous food products in sub-Saharan Africa [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…e high prevalence of Candida and Saccharomyces in the products is consistent with studies elsewhere that reported them as the most dominant yeasts in many foods in sub-Saharan Africa [25,26]. Reports have shown that S. cerevisiae is the dominant yeast in the fermentation of most indigenous food products in sub-Saharan Africa [27,28].…”
Section: Diversity Of Yeast and Mould In Productssupporting
confidence: 87%
“…Galactomyces geotrichum was also isolated from the fermented food products. Galactomyces geotrichum has been listed as among the yeasts that occur in African fermented food products in a review by Johansen et al (2019). Therefore, this present work has confirmed the biodiversity of yeasts that are associated with Nigerian traditional fermented food products.…”
Section: Resultssupporting
confidence: 77%
“…predominant microbial communities of African spontaneously fermented foods from cereals and milk (Akabanda et al, 2013;Hayford, Petersen, Vogensen, & Jakobsen, 1999;Jespersen, 2003;Johansen et al, 2019;Owusu-Kwarteng et al, 2012). Yeast species such as Kluyveromyces marxianus and Saccharomyces cerevisiae have been recently identified in sorghum-and maize-based mawè, a fermented food in Benin (Houngbédji et al, 2018).…”
mentioning
confidence: 99%